Considerations for mission leadership in United Nations peacekeeping operations. - Challenges Project; International Forum for the Challenges of Peace Operations (Stockholm : International Forum for the Challenges of Peace Operations, 2010)
Seeks to identify some of the principles and concepts underpinning the core functions of multidimensional peacekeeping. It is a study with many purposes, as it may serve as an introduction or training material for new practitioners, as well as a reminder or reference document for experienced peacekeeping leaders. While it is primarily intended for the mission leadership team, it may be of interest to anyone wishing to gain a better understanding of the host of issues and challenges facing contemporary peacekeeping operations.
Leadership, coordination and integration -- Cross-cutting issues and mission management considerations -- Facilitating and supporting the political process -- Creating a secure and stable environment -- Strengthening rule of law with respect for human rights -- Promoting social and economic recovery.
Keywords: United Nations -- Peacekeeping forces; Peace-building.; Armed Forces -- Stability operations; Combined operations (Military science)